Impact of social media-supported flipped classroom on English as a foreign language learners’ writing performance and anxiety - Zhao, Xiangfeng; Yang, Yanping (Frontiers in Psychology, 2023)
As flipped classroom has received much attention from researchers and educators, some scholars have investigated the effectiveness of this teaching mode in various English as a foreign language (EFL) settings; however, such an instruction mode has been under-investigated in the Chinese EFL context. Therefore, the current study examined a flipped course’s impact on Chinese EFL learners’ writing performance and anxiety utilizing a pretest-posttest non-equivalent group quasi-experimental design. First, it selected a sample of 50 Chinese EFL learners from two intact language school classes as the participants via the convenience sampling method. Then, it randomly assigned participants of these two intact classes to a control group (n = 24), taught based on the traditional method of writing instruction, and an experimental group (n = 26), instructed based on social media-supported flipped instruction. The study used two writing tasks and a writing anxiety inventory to gather the data from the participants. The descriptive and inferential statistics results showed that the experimental group—taught based on flipped writing instruction—significantly enhanced their writing performance. Moreover, they revealed that the flipped course substantially reduced participants’ writing anxiety. Implications of such findings have been elaborated for EFL research and practice.